Virtue male sling for post‐prostatectomy stress incontinence: a prospective evaluation and mid‐term outcomes. (1st November 2016) - Ferro, Matteo; Bottero, Danilo; D'Elia, Carolina; Matei, Deliu Victor; Cioffi, Antonio; Cozzi, Gabriele; Serino, Alessandro; Cordima, Giovanni; Bianchi, Roberto; Incarbone, Piero Giacomo; Brescia, Antonio; Musi, Gennaro; et al.
Abstract : Objective: To evaluate the efficacy and safety of the Virtue ® male sling (Coloplast, Humlebaek, Denmark) in a cohort of patients affected by post‐prostatectomy stress urinary incontinence (SUI). Methods: All 29 consecutive patients treated with a Virtue male sling at our Institution between July 2012 and October 2013 were included in the present prospective, non‐randomized study. Patients were evaluated preoperatively and at 1, 3, 6, 12, 24 and 36 months after surgery using a 24‐h pad weight test, the International Consultation on Incontinence short‐form questionnaire (ICIQ‐SF), Urinary Symptom Profile (USP) questionnaire, a bladder diary, uroflowmetry and the Patient Global Impression of Improvement (PGI‐I) and Patient Global Impression of Severity questionnaires. Results: The mean patient age was 65.5 years. A total of 72.4% of patients had preoperative mild incontinence (1–2 pads/day), while nine patients used 3–5 pads/day. There were a total of 17 complications, which occurred in 29 patients (58.6%); all were Clavien–Dindo grade I. At 12‐month follow‐up patients showed a significant improvement in 24‐h pad test (128.6 vs 2.5 g), number of pads per day (2 vs 0), ICIQ‐SF score (14.3 vs 0.9) and USP score for SUI (4 vs 0), and outcomes remained stable at 36 months. At last follow‐up, the median score on the PGI‐I questionnaire was 1 (very much better). Conclusion: The Virtue male sling is an effective treatment option for low to moderate post‐prostatectomy incontinence.